The Proposed Specifiers for Conduct Disorder (PSCD) Scale: Factor Structure and Validation of the Self-Report Version in a Forensic Sample of Belgian Youth. (June 2023) - Colins, Olivier F.; Bisback, Athina; Reculé, Cedric; Batky, Blair D.; López-Romero, Laura; Hare, Robert D.; Salekin, Randall T.
This is the first study to test the psychometric properties of the self-report version of the Proposed Specifiers for Conduct Disorder (PSCD) in detained youth. The PSCD is a measure of the broad psychopathy construct, with grandiose-manipulative, callous-unemotional, daring-impulsive, and conduct disorder (CD) components. Participants (227 males) completed the PSCD along with other measures, including a diagnostic interview to assess Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM- 5) CD. Results support the PSCD's proposed hierarchical four-factor structure. Correlations with an alternate measure of psychopathy and symptoms of CD support the convergent validity of PSCD scores. PSCD scores showed positive associations with criterion variables of emotional and regulatory functioning, aggression, substance use, and school problems. Finally, PSCD scores were unrelated to anxiety and depression, supporting the PSCD's discriminant validity. Findings indicate that the PSCD is a promising measure for assessing psychopathic traits in detained male adolescents, though its incremental validity is in need of further scrutiny.